If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2log(3x + 5) = 4 Reorder the terms: 2glo(5 + 3x) = 4 (5 * 2glo + 3x * 2glo) = 4 (10glo + 6glox) = 4 Solving 10glo + 6glox = 4 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -4 + 10glo + 6glox = 4 + -4 Combine like terms: 4 + -4 = 0 -4 + 10glo + 6glox = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-2 + 5glo + 3glox) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-2 + 5glo + 3glox)' equal to zero and attempt to solve: Simplifying -2 + 5glo + 3glox = 0 Solving -2 + 5glo + 3glox = 0 Move all terms containing g to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 5glo + 2 + 3glox = 0 + 2 Reorder the terms: -2 + 2 + 5glo + 3glox = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 5glo + 3glox = 0 + 2 5glo + 3glox = 0 + 2 Combine like terms: 0 + 2 = 2 5glo + 3glox = 2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -19.5=9.5x-5.5x | | 12(x+1)=-3 | | 22=x-7.8 | | 14-5x=-52 | | 121=4x+7 | | 4(x-5)=2(x+2) | | x+15+75=x | | (x-lnx*2x)/x^4 | | -3x+8x=10 | | 2n-3/7=1n-2/5 | | x+15=x+75 | | -6x+8=-3x-10 | | 6x-3x=-15 | | x^2-2x=20.085 | | 3n-6n=-12 | | xsquared+6x+2=3 | | 5x+5-6x=1 | | -24=4(x+6) | | R-3-8=-12 | | y^2-16y-100=0 | | R-4-7r=-10 | | -3u-(-7)=-4 | | 4u+10=-5(u+7) | | 3x+x=2x-10 | | 3(9-3x)=27 | | 2(3a+9b)= | | 5.5(4.5b+6)=22.5+7b | | 8(y-3)=4y+4 | | 2x^3(x+1)=3x^2-(x-6) | | 2x-11=7x+6 | | 36=w+5w | | 5(8+7x)=390 |